Experimental Study of Electron Emission Characteristics of a Surface Flashover Trigger in a Low Pressure Environment - Hu, Shangmao (上茂 胡); Yao, Xueling (学玲 姚); Chen, Jingliang (景亮 陈) (Plasma science & technology, 2010)
Characteristics of electron emission induced by a surface flashover trigger device in a low-pressure trigger switch were investigated. A test method to measure the emitted charges from the trigger device was developed, and the factors affecting the emitted charges were analyzed. The results indicated that the major emitted charges from the trigger device were induced by surface plasma generated by surface flashover occurring on the trigger dielectric material. The emitted charges and the peak emission current increased linearly with the change in the trigger voltage and bias voltage. The emitted charges collected from the anode were affected by the gap distance. However, the emitted charges were less affected by the anode diameter. Furthermore, the emitted charges and the peak emission current decreased rapidly with the increase in gas pressure in a range from 0 Pa to 100 Pa, and then remained stable or changed slightly when the increase in gas pressure up to 2400 Pa.